CREATIVE CHARACTER DEVELOPMENT AND MANAGEMENT: INSIGHTS ON INNOVATION IMPROVEMENT IN COOPERATIVES - Witarsa, Witarsa (FASTABIQ: JURNAL STUDI ISLAM, 2023)
This study explores creative character development on cooperative managers and administrators and its role in fostering innovation within Pontianak cooperatives. Through a mixed methods approach, combining quantitative and qualitative techniques, data was gathered from 300 people serving in 18 cooperatives within Pontianak city. The findings revealed that internal factors, such as an individual's potential to be creative, as well as external factors from their organizations and the environment, influenced creativity development. Negative influences like conservatism were identified, while positive factors like motivation, intellect, and emotions facilitated creativity. Effectively managing these factors is vital for enhancing cooperative managers' and administrators' creativity, leading to improved management strategies and innovative solutions. This study could be of relevance to designers of  training programs to foster innovation in cooperatives. Keywords: Creativity development; character; cooperatives management.